The Management of Natural Resources in 10 – 14 AD, The Hindu-Buddhist Era, based on Old Javanese Inscription in the Malang Highlands, East Java: Environmental Archeology Study - Suprapta, Blasius (Sejarah dan Budaya: Jurnal Sejarah, Budaya, dan Pengajarannya, 2020)
Abstract: Based on geological studies, the Malang Highlands, East Java, Indonesia is a former ancient lake that dried up and turned into a wide and fertile plateau. Such natural conditions allow the growth and development of Hindhu-Buddhist civilization in 10 - 14  AD, namely the socio-cultural life of a well-ordered community. This includes the structure of natural resource management by the state and society. Around 19 old Javanese Inscription certificates were issued by the king at that time. Some of these inscriptions contain the standard rules of the kingdom in relation to the management of natural resources, but so far there has not been an in-depth study of the rules of natural resource management in this region. In connection with this problem, the need to conduct a study of natural resource management based on Old Javanese Inscription through an environmental approach: Environmental Archeology. The study was conducted by literature study, toponymy analysis, geographical spatial analysis on topographical maps, and interpretation of natural resource management, through an environmental management approach. The results showed that there were rules for felling trees in primary forest areas, state forest management for the benefit of maintaining sacred buildings and there were rules for the sale and purchase of endemic plants, namely spices. Abstrak: Berdasarkan studi geologi, Dataran Tinggi Malang, Jawa Timur, Indonesia merupakan bekas danau purba yang mengering dan berubah menjadi dataran tinggi yang luas dan subur. Kondisi alam yang demikian memungkinkan tumbuh dan berkembangnya peradaban Hindhu-Budha pada 10 - 14 Masehi, yaitu kehidupan sosial budaya masyarakat yang tertata rapi. Ini termasuk struktur pengelolaan sumber daya alam oleh negara dan masyarakat. Sekitar 19 akte Prasasti Jawa kuno dikeluarkan oleh raja saat itu. Beberapa prasasti tersebut memuat aturan baku kerajaan dalam kaitannya dengan pengelolaan sumber daya alam, namun sejauh ini belum ada kajian yang mendalam tentang aturan pengelolaan sumber daya alam di wilayah ini. Sehubungan dengan masalah tersebut, perlu dilakukan kajian pengelolaan sumber daya alam berbasis Prasasti Jawa Kuno melalui pendekatan lingkungan: Arkeologi Lingkungan. Penelitian dilakukan dengan studi literatur, analisis toponimi, analisis spasial geografis pada peta topografi, dan interpretasi pengelolaan sumber daya alam, melalui pendekatan pengelolaan lingkungan. Hasil penelitian menunjukkan adanya aturan penebangan pohon di kawasan hutan primer, pengelolaan hutan negara untuk kepentingan pemeliharaan bangunan suci dan terdapat aturan jual beli tanaman endemik yaitu rempah-rempah.